2019
DOI: 10.3389/fphys.2019.00044
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of a Novel Integrative Motor Performance Testing Course for Seniors: The “Agility Challenge for the Elderly (ACE)”

Abstract: Background: Assessing traditional neuromuscular fall risk factors (i.e., balance, gait, strength) in the elderly has so far mainly been done independently. Functional and integrative testing approaches are scarce. The present study proposes an agility course for an integrative assessment of neuromuscular and also cardiocirculatory capacity in seniors – and tests its criterion validity and reliability.Methods: Thirty-six seniors (age: 69.0 ± 2.8 years; BMI: 25.4 ± 3.5 kg/m2; sex: 19 males/17 females; weekly phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 32 publications
7
14
0
Order By: Relevance
“…Plisky and colleagues reported CoV of 5.9% for the composite score of the Y-balance test (Plisky et al, 2009) and a minimal detectable change of 0.05 for the composite score in older adults (Sipe et al, 2019). We found a similar CoV in our unpublished data of 5.1% (Lichtenstein et al, 2019).…”
Section: Methodssupporting
confidence: 88%
See 3 more Smart Citations
“…Plisky and colleagues reported CoV of 5.9% for the composite score of the Y-balance test (Plisky et al, 2009) and a minimal detectable change of 0.05 for the composite score in older adults (Sipe et al, 2019). We found a similar CoV in our unpublished data of 5.1% (Lichtenstein et al, 2019).…”
Section: Methodssupporting
confidence: 88%
“…The accelerometer records data at 50 Hz. In our previous study (Lichtenstein et al, 2019), we observed an average CoV of 7.7% for this procedure (unpublished data).…”
Section: Methodssupporting
confidence: 55%
See 2 more Smart Citations
“…It considers complex functional tasks, including stop-and-go as well as cutting movements, changes of direction, perceptional challenges, decision making, reaction tasks and, thereby, stresses the need for continuous progression of difficulty and complexity of exercises. A test assessing the agility construct was developed and validity with regard to traditional fall risk Agility-based exercise training compared to traditional strength and balance training in older adults: a pilot randomized trial 3 OSF Generated citation factors was recently assessed [13]. The aim of the current study was to apply the agility framework to an exercise training intervention and compare the efficacy to a traditional exercise training intervention targeting particularly strength and balance in older adults.…”
Section: Introductionmentioning
confidence: 99%